The Pícaro Transfigured: Gavroche in Hugo's Misérables. (1st October 2016) - Porter, Laurence M.
Abstract : Hugo's characterization of Gavroche transforms and transcends traditional picaresque depictions of youthful, socially marginal antiheroes. Like them, Gavroche is an abandoned child who must learn to live by his wits. However, instead of parading him through an episodic structure that serves as a satiric portrait gallery of various social milieux, Hugo makes Gavroche's five appearances conform to the basic structure of a tragedy with introduction, noeud [complications], crise [a decisive resolve by the hero], moment culminant, and denouement in which Gavroche achieves the sublime by sacrificing his life for an ideal. Thus he, along with Fantine and Éponine, illustrates the moral superiority which the humblest members of society may achieve. This message is masked by the intense dynamism of Gavroche ('le mouvement nuit à la dignité'), the sordid conditions under which he must live, and by his grotesque, ebullient verbal creativity.